2023
DOI: 10.33517/rue2023v18n1a8
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la hospitalización y la mortalidad por VIH en Brasil, 2016-2020

Abstract: the care network with regard to the provision of health actions and services, as well as the socioeconomic and behavioral conditions that influence the course of HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Especially in Amazonas and Acre, where high-burden clusters have been observed, geographical barriers should be considered, which may culminate in late access to HIV diagnosis or difficulty in following up people living with the virus 43 . A study conducted in the North region, the largest in territorial terms, showed that the coverage of primary health care services predominates in the host cities of the states 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in Amazonas and Acre, where high-burden clusters have been observed, geographical barriers should be considered, which may culminate in late access to HIV diagnosis or difficulty in following up people living with the virus 43 . A study conducted in the North region, the largest in territorial terms, showed that the coverage of primary health care services predominates in the host cities of the states 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Especialmente no Amazonas e no Acre, onde foram visualizados clusters de alta carga, deve-se considerar as barreiras geográficas para a população, o que pode culminar no acesso tardio ao diagnóstico de HIV ou na dificuldade do seguimento das pessoas vivendo com o vírus 43 . Estudo realizado na região Norte, a maior em termos territoriais, demonstrou que a cobertura dos serviços de atenção primária à saúde predomina nas cidades-sede dos estados 44 .…”
Section: Discussionunclassified